2021
DOI: 10.2174/1573396317666210909155024
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Nucleated Red Blood Cells in Neonates with and without Retinopathy

Abstract: Introduction: Retinopathy of prematurity (ROP) is one of the reasons of blindness in children. Numerous predisposing factors have been reported, including prematurity and oxygen therapy. We assessed the number of nucleated red blood cells in neonates with ROP and compared it with the patients that didn t suffer from the situation. Methodology: This case-control study was performed on 151 neonates with birth weight<1500 gr and/or gestational age< 32 weeks that were born in Ghaem Hospital of Mashhad f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Numerous studies have revealed that NRBCs can be used as an important indicator of the presence and duration of intrauterine hypoxia or the assessment of the severity and early outcome of perinatal asphyxia [16,17]. NRBCs are also a sensitive indicator of mortality among preterm infants and the prognosis of conditions such as retinopathy of prematurity (ROP), bronchopulmonary dysplasia, necrotizing enterocolitis, or sickle cell disease [4,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have revealed that NRBCs can be used as an important indicator of the presence and duration of intrauterine hypoxia or the assessment of the severity and early outcome of perinatal asphyxia [16,17]. NRBCs are also a sensitive indicator of mortality among preterm infants and the prognosis of conditions such as retinopathy of prematurity (ROP), bronchopulmonary dysplasia, necrotizing enterocolitis, or sickle cell disease [4,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Other possible important factors include: apnea, mechanical ventilation, anemia and need for blood transfusion, vitamin deficiencies, intraventricular hemorrhage, sepsis, acidosis, hypotension, pneumothorax, chronic lung diseases, high levels of arterial carbon dioxide, seizure, and bradycardia. 5,6 Effective early identification of high risk infants and examination of their retina has been proven to reduce the complications of RoP. 7,8 Maintaining normal blood levels of calcium and phosphorus is the main biological function of vitamin D. Vitamin D promotes an overall boost in the immune system.…”
Section: Introductionmentioning
confidence: 99%